KONSTRUKSI MASYARAKAT KOTA MADIUN TENTANG KEKERASAN ANAK SELAMA PANDEMI COVID-19 - Samaragravira, Ayu (Paradigma, 2022)
Abstract Child violence is one of the social problems in Indonesia that is difficult to handle, so that when COVID-19, based on the PPA Symphony data, the level of child violence in Indonesia reached 3,314. Cases of child violence spread throughout Indonesia, one of which is Madiun City. Based on case report data at the Integrated Service Center (PPT) in the P3A sector, the number of cases of child domestic violence and non-domestic violence from January to December 2020 reached 10 cases. The number of cases of child violence that is happening today proves that there are still people who do not understand about violence against children. In addition, there are still many parents who have the assumption that if they are not given physical and verbal firmness, children are difficult to control. This study uses a qualitative method with the perspective of Social Construction theory by Peter L. Berger. The results of this study prove that child abuse during the covid-19 pandemic occurs because of changes in life that make people depressed so that they vent their frustration on children. The community knows that child abuse should not be carried out. Their understanding comes from social interactions, namely family socialization, religious knowledge, and cultural construction. After going through three simultaneous stages of externalization, objectification and internalization, the community finally made their own choices in educating children